PENGARUH STRUKTUR MODAL, PENGUNGKAPAN EMISI KARBON DAN, BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN - Najwa Az-Zahra; Dwi Winarni; Azmi Fitriati; Rina Mudjiyanti (JURNAL ILMIAH EDUNOMIKA, 2026)
This research aims to analyze the influence of capital structure, environmental costs, and carbon emission disclosure on the financial performance of energy companies listed on the Indonesia Stock Exchange from 2022 to 2024. This study uses panel data analysis with a quantitative approach, employing the Random Effect model. The research data is obtained from annual reports and sustainability reports from a total of 39 companies, resulting in 117 data observations. The data was processed using STATA software. The results indicate that capital structure (DAR) and environmental costs have a positive and significant effect on financial performance, while carbon emission disclosure negatively impacts financial performance. Proportional use of debt and increased investment in the environment can strengthen financial performance. Findings related to disclosure of carbon emissions emphasize the need for improved quality and standards of carbon emission reporting in Indonesia.